Comparative Transcriptome and Metabolic Profiling Analysis of Buckwheat (Fagopyrum Tataricum (L.) Gaertn.) under Salinity Stress - Weibo Ma; Jae Kwang Kim; Caihua Jia; Feifan Yin; Hyo Jin Kim; Waheed Akram; Xuebo Hu; Xiaohua Li (Metabolites, 2019)
Tartary buckwheat (Fagopyrum tataricum (L.) Gaertn.) is a nutritional crop, which has high flavonoid content. However, buckwheat is a salt sensitive glycophyte cereal crop and the growth and grain yield of buckwheat are significantly affected by soil salinity. In this study, we performed a comprehensive analysis of the transcriptome and metabolome of salt treated-buckwheat to understand the effects of salinity on buckwheat. A total of 50,681,938 clean reads were acquired from all samples. We acquired 94,950 unigenes with a mean length of 1133 bp and N50 length of 1900 bp assembly. Of these, 63,305 unigenes (66.7%) were matched in public databases. Comparison of the transcriptome expression patterns between control and salt treated groups showed that 4098 unigenes were up-regulated and 3292 unigenes were down-regulated significantly. Further, we found that genes involved with amino acid, lipid and nucleotide metabolism were most responsive to salt stress. Additionally, many genes involved in secondary metabolite biosynthesis changed significantly following treatment. Those affected included phenylpropanoid biosynthesis and flavonoid biosynthesis. Chromatographic analysis was used to examine the differences in concentration of flavonoids, carotenoids, amino acids and organic acids in the samples following treatment. There was a significant increase in rutin (12.115 mg/g dry weight), following salt stress; whereas, six carotenoids (lutein, zeaxanthin, 13Z-β-carotene, α-carotene, E-β-carotene and 9Z-β-carotene) did not significantly respond to salt stress. Ultimately, our data acts as a valuable resource for future research on buckwheat and can be used as the basis for future analysis focused on gene-to-metabolite networks in buckwheat.